Organophosphate insecticide susceptible test and transovarial transmission detection of dengue virus on Aedes aegypti in Kendari - Tri Baskoro Tunggul Satoto, Muhaimin Saranani Sitti Rahmah Umniyati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2013)
Dengue Fever (DF) is a disease caused by the dengue virus that transmitted by Aedes aegypti(Ae. Aegypti) and Ae. albopictus. Dengue fever is now one of the most important public healthproblems in Indonesia. Vector control using insecticides is the most important strategy to controlthe DF. Massal fogging and selective abatisation have implementedd intensively to control Ae.aegypti. However after its a long time implementation, mosquitoes resistance and transovarialtransmission have been reported. The aim of the study was to evaluate the susceptibility statusof Ae. aegypti to organophosphate and its ability to transovarial transmit degue virus in KendariCity, South East Sulawesi. This was a observational study using cross-sectional design conductedin high endemic areas (Kadia Village) and low endemic areas (Kambu Village). Susceptibilitystatus of Ae. aegypti larvae from F1âs egg generation was evaluated by biochemic assay, whereasthe transovarial transmission of dengue virus of adult female Ae. aegypti was evaluated byimmunohistochemistry method using head squash preparation. The results showed that the Ae.aegypti larvae resistant was higher in high endemic areas (Kadia Village) (83.33%) than in lowendemica areas (Kambu Village) (60.00%). In addition, transovarial transmission index (TTI) ofAe. aegypti dengue virus in the high endemic areas (26%) was significantly higher than in thelow endemic areas (12%) (p<0.05). In conclusion, the Ae. aegypti larvae resitance toorganophosphate as well as the TTI in high endemic areas is higher than in low endemic area inKendari, Sout East Sulawesi.